Construction of a Standardized Tongue Image Database for Diagnostic Education: Development of a Tongue Diagnosis e-Learning System - Segawa, Makoto; Iizuka, Norio; Ogihara, Hiroyuki; Tanaka, Koichiro; Nakae, Hajime; Usuku, Koichiro; Hamamoto, Yoshihiko (Frontiers in Medical Technology, 2021)
Tongue examination is an important diagnostic method for judging pathological conditions in Kampo, but it is not easy for beginners to learn the diagnostic technique. One reason is that there are few objective diagnostic criteria for tongue examination findings, and the educational method for tongue examination is not standardized in Japan, warranting the need for a tongue image database for e-learning systems that could dramatically improve the efficiency of education. Therefore, we constructed a database consisting of tongue images whose findings were determined on the basis of votes given by five Kampo medicine specialists (KMSs) and confirmed the educational usefulness of the database for tongue diagnosis e-learning systems. The study was conducted in the following five steps: development of a tongue imaging collection system, collection of tongue images, evaluation and annotation of tongue images, development of a tongue diagnosis e-learning system, and verification of the educational usefulness of this system. Five KMSs evaluated the tongue images obtained from 125 participants in the following eight aspects: (i) tongue body size, (ii) tongue body color, (iii) tongue body dryness and wetness, (iv) tooth marks on the edge of the tongue, (v) cracks on the surface of the tongue, (vi) thickness of tongue coating, (vii) color of tongue coating, and (viii) dryness and wetness of tongue coating. Medical students (MSs) were given a tongue diagnosis test using an e-learning system after the lecture on tongue diagnosis. The cumulative and individual match rates (%) of diagnoses among the five KMSs were as follows (individual match rates of 5/4/3 evaluators are shown in parentheses, respectively); (i) 93% (26/26/40); (ii) 83% (10/21/52); (iii) 89% (14/34/41); (iv) 89% (6/35/47); (v) 97% (24/35/38); (vi) 85% (7/22/56); (vii) 88% (15/38/35); and (viii) 75% (5/20/50). The test showed that the tongue diagnosis ability of MSs who attended a lecture on tongue diagnosis was almost the same as that of KMSs. We successfully constructed a tongue image database standardized for training specialists on tongue diagnosis and confirmed the educational usefulness of the e-learning system by using a database. This database will contribute to the standardization and popularization of Kampo education.